Nepenthes gymnamphora Nees. DI TAMAN NASIONAL GUNUNG HALIMUN DAN PENYEBARANNYA DI INDONESIA - Mansur, Muhammad (BERITA BIOLOGI, 2002)
The preliminary study of Nepenthes gymnamphora Nees. was carried out on May 2001 in Halimun Mountain National Park. West Java by survei method and direct observation in its original habitat. Some samples were collected for morphological study, taxonomical identification and specimen collections for Herbarium Bogoricnse, Bogor. N. gymnamphora founded on summit of Mt. Kendeng (1020 m asl) and Wales area in Bogor-Sukabumi border (1120 m asl). Habitat, morphology, conservation and their distribution in Indonesia is explained.